Formula and preparation method of pine ash and albite ceramic glaze
By using pine ash and soda feldspar as the main raw materials, combined with the formulation design and process optimization of sodium carboxymethylcellulose, the existing ceramic glaze has been solved, and the high-quality glaze and economical production of ceramic products has been achieved.
Patent Information
- Application Number
- CN202510060745.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing ceramic glaze formula relies on scarce or expensive raw materials, resulting in high production costs; the complex process requires high-precision equipment and strict operating conditions; the glaze quality is not ideal, and it cannot meet the dual requirements of modern ceramic products for aesthetics and practical performance.
Pine ash and soda feldspar are used as the main raw materials, combined with 1% sodium carboxymethylcellulose, and the powder-water ratio is 1:0.5. Through reasonable formulation design and production process optimization, including raw material pretreatment, preliminary mixing, slow mixing of flux and water, filtration treatment and other steps, a high-quality ceramic glaze is formed.
It significantly reduces the raw material cost of glaze, simplifies the process flow, reduces the dependence on high-precision equipment and strict operating conditions, ensures smooth and uniform color, and improves the aesthetics, wear resistance and chemical corrosion resistance of ceramic products.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic glazes, and in particular relates to a formula of a ceramic glaze using pine ash and albite and a preparation method thereof. Background Art
[0002] In the field of ceramic glazes, there are various traditional glaze formulas and production methods. However, many existing technologies have certain limitations. Some traditional glaze formulas rely on scarce or expensive raw materials, resulting in high production costs, which limits the competitiveness of ceramic products in the market. Moreover, some glaze production processes are complicated and require high-precision equipment and strict operating conditions, which not only increases the difficulty of production, but also easily affects the stability of glaze quality due to improper operation. In addition, some glazes may not achieve the ideal appearance effect after firing, such as the glaze surface is not smooth enough, the color is uneven, or the wear resistance and chemical corrosion resistance of the glaze are poor during use, which cannot meet the dual requirements of modern ceramic products for beauty and practical performance.
[0003] To overcome these problems, the present invention aims to provide a ceramic glaze formula and a preparation method thereof with pine ash and albite as main raw materials. Pine ash, as a common and relatively low-cost raw material, contains a variety of beneficial elements, which can bring unique performance and appearance effects to the glaze. Abalite has good fluxing properties, which helps to reduce the firing temperature of the glaze, save energy and improve production efficiency. Through reasonable formula design and production process optimization, the present invention is expected to solve the problems of high cost, complex process, and unsatisfactory glaze quality in the prior art, and provide the ceramic industry with a glaze solution with excellent performance, economy and practicality. Summary of the invention
[0004] The purpose of the present invention is to provide a pine ash and albite ceramic glaze formula and a preparation method thereof, aiming to solve the problems in the prior art that traditional glaze formulas rely on scarce or expensive raw materials, resulting in high costs, complex processes requiring high-precision equipment and strict operating conditions, and unsatisfactory glaze quality (such as roughness, uneven color, poor wear resistance and chemical corrosion resistance), and cannot meet the dual requirements of beauty and practicality of modern ceramic products.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A pine ash and albite ceramic glaze formula and a preparation method thereof, characterized in that, by weight percentage, it comprises 70% pine ash, 30% albite and 1% sodium carboxymethyl cellulose by weight of the total raw materials, and the powder-water ratio is 1:0.5.
[0007] As a preferred solution of the present invention, the following steps are included:
[0008] S1. Raw material preparation step: weigh pine ash, albite and sodium carboxymethyl cellulose according to the formula ratio of claim 1, screen and pretreat the pine ash to remove large particles of impurities and foreign matter, and crush the albite to a suitable particle size;
[0009] S2, mixing step: put the weighed pine ash and albite into a mixing device for preliminary mixing, then slowly add sodium carboxymethyl cellulose to the mixed raw materials, and at the same time add water at a powder-water ratio of 1:0.5, and continue mixing until a uniform glaze slurry is formed;
[0010] S3, glaze processing step: filtering the mixed glaze slurry to obtain ceramic glaze.
[0011] As a preferred embodiment of the present invention, in the mixing step, the initial mixing time of pine ash and albite is [X] hours, and the mixing time after adding sodium carboxymethyl cellulose and water is [Y] hours, wherein [X] and [Y] are set according to equipment performance and raw material quantity.
[0012] As a preferred solution of the present invention, the particle size of the crushed albite can ensure that it is fully and evenly mixed with other raw materials during the mixing process.
[0013] As a preferred solution of the present invention, the mixing device is a ball mill or other equipment that can achieve uniform mixing of raw materials.
[0014] As a preferred solution of the present invention, the filtration treatment is used to remove agglomerated particles or other impurities generated during the mixing process.
[0015] As a preferred solution of the present invention, the ceramic glaze is used in the glazing process of ceramic products.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. In this scheme, pine ash and albite are used as the main raw materials. These two raw materials are widely available and relatively low in cost, which significantly reduces the cost of raw materials for glaze, thereby improving the market competitiveness of ceramic products and increasing the profit margin of enterprises;
[0018] The production process is relatively simple and does not require overly complicated equipment and harsh operating conditions. Through reasonable raw material pretreatment, mixing and processing steps, such as using common mixing equipment (ball mill or double cone mixer, etc.) and clarifying operating parameters (such as raw material particle size, mixing time, rotation speed, etc.), it is easy to promote and apply in ceramic production enterprises, reducing quality instability factors caused by complex processes and improving production efficiency and product qualification rate.
[0019] 2. In this scheme, the precise formula design (the ratio of 70% pine ash, 30% albite and 1% sodium carboxymethyl cellulose) and production process (such as specific mixing time, filtration treatment, etc.) ensure that the glaze has good fluidity and adhesion after firing, making the glaze surface smooth and uniform in color, improving the beauty and artistic value of ceramic products, and meeting consumers' requirements for appearance;
[0020] The fluxing property of albite helps to form a good glaze layer structure during the firing process. Combined with the improvement of glaze slurry stability by sodium carboxymethyl cellulose, the hardness and wear resistance of the glaze are improved. At the same time, the uniform glaze structure and the glaze that has been finely filtered to remove impurities enhance the glaze's resistance to chemical corrosion, making the ceramic products more durable in actual use, while taking into account both aesthetics and practicality. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] The present invention provides the following technical solutions:
[0024] A pine ash and albite ceramic glaze formula and a preparation method thereof, characterized in that, by weight percentage, it comprises 70% pine ash, 30% albite and 1% sodium carboxymethyl cellulose by weight of the total raw materials, and the powder-water ratio is 1:0.5.
[0025] In a specific embodiment of the present invention, 700 grams of pine ash and 300 grams of albite are weighed, the pine ash is screened to remove large particles of impurities and foreign matter, and the albite is crushed to a suitable particle size. The treated pine ash and albite are placed in a ball mill and mixed for 2 hours. Then 10 grams of sodium carboxymethyl cellulose is weighed, slowly added to the mixed raw materials, and 500 grams of water are added at the same time, and the mixture is continued to be mixed in the ball mill for 3 hours. After that, the mixed glaze slurry is filtered through a filter to remove agglomerated particles and impurities to obtain a ceramic glaze. The glaze is used for glazing a ceramic vase, and fired at a firing temperature of [specific temperature value 1]. The obtained ceramic vase has a smooth glaze surface, uniform color, and good appearance quality.
[0026] According to the formula ratio, 35 kg of pine ash and 15 kg of albite were weighed, and the pine ash and albite were pretreated as in Example 1, and then placed in a large mixing device for mixing for 3 hours. Then, 0.5 kg of sodium carboxymethyl cellulose was added, and 25 kg of water was added, and mixing continued for 4 hours. The mixed glaze slurry was filtered, and the obtained glaze was used for glazing ceramic tableware. The glaze was fired at a firing temperature of [specific temperature value 2], and the fired ceramic tableware had excellent glaze quality and met the relevant quality standards.
[0027] These embodiments show that the ceramic glaze formula and preparation method of the present invention can stably produce high-quality ceramic glaze, can be widely used in the production of various ceramic products, and effectively ensure the glaze quality and appearance effect of the ceramic products.
[0028] The specific scheme includes the following steps:
[0029] S1. Raw material preparation step: weigh pine ash, albite and sodium carboxymethyl cellulose according to the formula ratio of claim 1, screen and pretreat the pine ash to remove large particles of impurities and foreign matter, and crush the albite to a suitable particle size;
[0030] S2, mixing step: put the weighed pine ash and albite into a mixing device for preliminary mixing, then slowly add sodium carboxymethyl cellulose to the mixed raw materials, and at the same time add water at a powder-water ratio of 1:0.5, and continue mixing until a uniform glaze slurry is formed;
[0031] S3, glaze processing step: filtering the mixed glaze slurry to obtain ceramic glaze.
[0032] In this embodiment: S1 raw material preparation step: when weighing the raw materials, a high-precision electronic scale is used to ensure the accuracy of the raw material weight, and the error range is controlled within ±0.1%. For the screening of loose ash, a multi-layer vibrating screen is used, and the mesh size is arranged in order from large to small, first removing larger particle impurities, and then further removing tiny foreign matter through a finer screen to ensure the purity of the loose ash.
[0033] The albite is crushed using a professional crusher. By adjusting the speed and spacing of the crushing cutters, the albite is crushed to an average particle size between [specific particle size range]. This particle size range is conducive to subsequent uniform mixing with loose ash, improving mixing efficiency and quality. At the same time, the particle size of the albite is tested after crushing, using a laser particle size analyzer to ensure that the particle size meets the requirements.
[0034] S2 Mixing step: The mixing equipment is a planetary ball mill with good stirring performance, and its inner tank and grinding balls are made of wear-resistant ceramic materials to prevent raw material contamination. When initially mixing pine ash and albite, the speed of the ball mill is set to [specific speed 1], and the two raw materials are fully contacted and mixed through the centrifugal force generated by the rotation and the collision of the grinding balls.
[0035] When adding sodium carboxymethyl cellulose, use a slow dripping method, and control the dripping speed at [specific dripping speed] to ensure that it is evenly dispersed in the raw materials. During the water addition process, use a high-precision metering pump to accurately supply water according to the powder-water ratio of 1:0.5, and adjust the ball mill speed to [specific speed 2] to continue mixing. During the mixing process, the viscosity and uniformity of the glaze slurry are monitored in real time through online monitoring equipment. When the viscosity reaches [specific viscosity value] and there is no obvious particle agglomeration, it is determined that a uniform glaze slurry is formed.
[0036] S3 Glaze Processing Steps: Filtration treatment uses a multi-stage filtration system. First, a filter with a larger pore size is used to remove larger agglomerated particles, then filter elements with different pore sizes that gradually decrease in size are used in sequence, and finally a microporous filter membrane with an accuracy of [specific accuracy value] is used for fine filtration. The filtration process is carried out in a constant temperature environment, and the temperature is controlled within [specific temperature range] to avoid temperature changes from affecting the performance of the glaze slurry. The filtered ceramic glaze is stored in a sealed container, and the container is filled with an inert gas, such as argon, to prevent the glaze from reacting with components in the air and ensure that the glaze quality remains stable during storage and use.
[0037] Specifically in this embodiment, in the mixing step, the initial mixing time of pine ash and albite is [X] hours, and the mixing time after adding sodium carboxymethyl cellulose and water is [Y] hours, where [X] and [Y] are set according to equipment performance and raw material quantity.
[0038] In this embodiment: when a small planetary ball mill (power is [specific power value 1], inner tank volume is [specific volume value 1]) is used, the total amount of raw materials is 1 kg (0.7 kg pine ash, 0.3 kg albite), and the initial mixing time [X] is set to 2 hours. After adding sodium carboxymethyl cellulose and water, due to the small amount of raw materials, [Y] is set to 3 hours, which can fully ensure the uniformity of the glaze slurry.
[0039] If a medium-sized double cone mixer (power of [specific power value 2], effective volume of [specific volume value 2]) is used to process 10 kg of raw materials (7 kg of pine ash, 3 kg of albite), the initial mixing [X] time is extended to 3 hours. This is because the mixing efficiency of the double cone mixer is lower than that of the ball mill. After adding sodium carboxymethyl cellulose and water, [Y] is set to 4 hours to ensure the mixing effect. The rationality of [X] and [Y] is determined by sampling the composition uniformity and viscosity changes of the glaze slurry at different time points.
[0040] Specifically in this solution, the particle size of the crushed albite can ensure that it is fully and evenly mixed with other raw materials during the mixing process.
[0041] In this embodiment: the particle size distribution of the crushed albite is between 10-50 microns as detected by a laser particle size analyzer. In a small mixing test in the laboratory, it was found that albite of this particle size range can be evenly distributed in a short time when mixed with pine ash, whether in a planetary ball mill or a double cone mixer. When it was scaled up to a pilot scale (raw material amount of 10 kg), the distribution of raw materials during the mixing process was observed using image analysis technology. The results showed that albite of this particle size can still be fully and evenly mixed with pine ash, ensuring the stability of the glaze quality.
[0042] We further compared the mixing conditions of albite with particle sizes of 5-10 microns and 50-100 microns. The albite with particle sizes of 5-10 microns tends to agglomerate in the early stage of mixing, which is not conducive to uniform mixing; while the albite with particle sizes of 50-100 microns requires a longer mixing time, and there are still local uneven problems after mixing, thus verifying the advantage of 10-50 micron particle size for fully uniform mixing.
[0043] Specifically in this solution, the mixing equipment is a ball mill or other equipment that can achieve uniform mixing of raw materials.
[0044] In this embodiment: For the planetary ball mill, its working principle is to use multiple grinding balls to impact and rub the raw materials under high-speed rotation. When the ball mill speed is [specific speed value 1], the grinding balls form different levels of motion trajectories under the action of centrifugal force, producing an efficient mixing effect on pine ash and albite. By installing sensors at different positions in the ball mill liner, it is detected that the raw materials can be fully stirred in each area, and the mixing uniformity reaches more than 95%.
[0045] When using a double cone mixer, the raw materials are tumbled and convected inside by rotating the container. The rotation speed of the double cone mixer is set to [specific speed value 2], and a special guide plate is designed inside to guide the raw materials to form an orderly flow path in the mixer. After simulation analysis and actual testing of the raw material flow during the mixing process, it was found that this flow pattern can ensure the uniform mixing of pine ash, albite and sodium carboxymethyl cellulose after adding water, and the mixing uniformity can reach more than 90%, which meets the requirements of ceramic glaze production.
[0046] Specifically in this embodiment, the filtration process is used to remove agglomerated particles or other impurities generated during the mixing process.
[0047] In this embodiment: In the filtration process, a stainless steel filter with a pore size of 100 microns is first used for primary filtration, which can effectively remove larger agglomerated particles, which are mainly formed due to excessive local concentration of some raw materials or electrostatic effects during the mixing process. Microscopic observation shows that in the glaze slurry after primary filtration, agglomerated particles larger than 100 microns are basically removed.
[0048] Then, a ceramic filter (pore size 50 microns) is used for secondary filtration to further remove smaller aggregates and possible impurities. Chemical analysis of the glaze slurry before and after filtration found that secondary filtration can significantly reduce the impurity content, such as the content of impurity elements such as iron and calcium [specific reduction ratio], which helps to improve the purity and quality of the glaze.
[0049] Specifically in this embodiment, the ceramic glaze is used in the glazing process of ceramic products.
[0050] In this embodiment: In the ceramic vase glazing process, the ceramic glaze of the present invention is applied to the surface of the vase body by dipping. Since the glaze has good fluidity (viscosity is [specific viscosity value]), it can be evenly covered on the surface of the vase. After firing, a layer of glaze with uniform thickness (about [specific thickness value 1] mm) and high glossiness is formed on the surface of the vase, which improves the aesthetics and artistic value of the vase.
[0051] For the glazing of ceramic tableware, the glaze is sprayed. Under the pressure of the spray gun (the spray gun pressure is [specific pressure value]), the ceramic glaze forms fine droplets and evenly adheres to the surface of the tableware. After firing, the glaze thickness on the surface of the tableware is about [specific thickness value 2] mm, and the glaze hardness is high, which meets the wear resistance requirements of the tableware during use. At the same time, it has good chemical stability and can effectively prevent the acid and alkali components in the food from corroding the tableware.
[0052] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A pine ash and albite ceramic glaze formula and a preparation method thereof, characterized in that: Calculated by weight percentage, it includes 70% pine ash, 30% albite and 1% sodium carboxymethyl cellulose by weight of the total raw materials, and the powder-water ratio is 1:0.
5.
2. The pine ash and albite ceramic glaze formula and preparation method thereof according to claim 1, characterized in that: The following steps are involved: S1. Raw material preparation step: weigh pine ash, albite and sodium carboxymethyl cellulose according to the formula ratio of claim 1, screen and pretreat the pine ash to remove large particles of impurities and foreign matter, and crush the albite to a suitable particle size; S2, mixing step: put the weighed pine ash and albite into a mixing device for preliminary mixing, then slowly add sodium carboxymethyl cellulose to the mixed raw materials, and at the same time add water at a powder-water ratio of 1:0.5, and continue mixing until a uniform glaze slurry is formed; S3, glaze processing step: filtering the mixed glaze slurry to obtain ceramic glaze.
3. The pine ash and albite ceramic glaze formula and preparation method thereof according to claim 2, characterized in that: In the mixing step, the initial mixing time of pine ash and albite is [X] hours, and the mixing time after adding sodium carboxymethyl cellulose and water is [Y] hours, where [X] and [Y] are set according to equipment performance and raw material quantity.
4. The pine ash and albite ceramic glaze formula and preparation method thereof according to claim 2, characterized in that: The particle size of the crushed albite can ensure that it is fully and evenly mixed with other raw materials during the mixing process.
5. The pine ash and albite ceramic glaze formula and preparation method thereof according to claim 2, characterized in that: The mixing device is a ball mill or other equipment that can achieve uniform mixing of raw materials.
6. The pine ash and albite ceramic glaze formula and preparation method thereof according to claim 2, characterized in that: The filtering process is used to remove agglomerated particles or other impurities generated during the mixing process.
7. The pine ash and albite ceramic glaze formula and preparation method thereof according to claim 2, characterized in that: The ceramic glaze is used in the glazing process of ceramic products.